Accuracy of iohexol plasma clearance for GFR-determination: a comparison between single and dual sampling - Yong Zhang (BMC Nephrology, 2018)
Abstract Background Current guidelines regarding plasma-sampling techniques for glomerular filtration rate (GFR) determination are inconsistent. Single-sample methods are commonly believed not to be precise enough to meet clinical demands. The present study compared the agreement between single- and dual- plasma sampling methods with a three-point plasma clearance of iohexol. Methods A total of 46 healthy volunteers and 124 chronic kidney disease (CKD) patients with varying degrees of renal dysfunction received 5 ml iohexol (300 mgI/ml) i.v. and plasma samples were drawn at 2-, 3- and 4-h post-injection. Plasma-iodine concentrations were detected by high-performance liquid chromatography (HPLC). Results Bias was similar among single-plasma sampling methods (SPSM) and dual-plasma sampling methods (DPSM). The best correlation was obtained from the 2- and 4-h DPSM (concordance correlation coefficient [CCC]: 0.9988) with none of the estimates differed by more than 30% from the reference GFR and only one (0.06%) estimate differed by more than 10% (P30, 100%; P10, 99.4%). SPSM using samples around 3- or 4-h demonstrated acceptable accuracy at a GFR level of ≥60 ml/min/1.73m2 (P30 = 100% and P10 > 75% for both measurements). Conclusion 4-h SPSM is advantageous in clinical practice in subjects with GFR ≥ 60 ml/min/1.73m2. For patients with an expected GFR < 60 ml/min/1.73m2, a prolonged sampling time is more reliable.